2019
DOI: 10.1177/1054137319885261
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Maturity and Self-Perception Among Adolescents Living With HIV—Need for Life-Skills Intervention

Abstract: Among Adolescents Living With HIV (hereby referred to as ALWH), emotional maturity and self-perception gain importance because they play a decisive role in the overall development into adulthood. This study examines the relationship between self-perception and emotional maturity among ALWH. The sample comprised of 92 male and female ALWH, aged 13 to 18 years. Self-Perception Questionnaire and Emotional Maturity Scale were the tools used. Descriptive and inferential statistics were used for analysis. Correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Considering that a higher score in the emotional maturity questionnaire means lack of emotional maturity, so with the improvement of the teacher's emotional maturity and its dimensions, the appropriate perception of the teacher's behavior increase. This finding was in line with the findings of Gupta & Sudhesh (2019), Malik & Kapoor (2014), Jafariharandi & Rajaiemoosavi (2019) and Sharifi Rigi & Bassaknezad (2018). In explaining the lack of a significant relationship between the dimensions of emotional instability, emotional return and personality collapse with the perception of teacher behavior, we can point to the specific characteristics of these dimensions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Considering that a higher score in the emotional maturity questionnaire means lack of emotional maturity, so with the improvement of the teacher's emotional maturity and its dimensions, the appropriate perception of the teacher's behavior increase. This finding was in line with the findings of Gupta & Sudhesh (2019), Malik & Kapoor (2014), Jafariharandi & Rajaiemoosavi (2019) and Sharifi Rigi & Bassaknezad (2018). In explaining the lack of a significant relationship between the dimensions of emotional instability, emotional return and personality collapse with the perception of teacher behavior, we can point to the specific characteristics of these dimensions.…”
Section: Discussionsupporting
confidence: 90%
“…There is no research on the relationship between emotional maturity and perception of teacher behavior and academic vitality, but the results of related studies indicate the relationship between emotional maturity and perception of teacher behavior and academic vitality. For example, Gupta & Sudhesh (2019) while researching concluded that emotional maturity had a positive and significant relationship with positive self-perception. The results of Malik & Kapoor (2014) showed that emotional maturity had a significant relationship with teacher effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The research component in the model facilitates academic efforts to improve awareness of unique psychosocial factors that play a role among ALWH. Research from this model includes a qualitative investigation into the stereotypes and stigma regarding HIV in India as experienced by the community (Gupta, 2018), a quantitative investigation of how resilience and well-being operates in ALWH (Sunaina et al, 2019), a quantitative study of self-perception and emotional maturity among ALWH (Gupta & Sudhesh, 2019a) and a resilience-based intervention to foster self-esteem and positive effects (Raj, 2018). In addition to the aim of academic publication to reach the wider scientific community, the studies have also been presented in international conferences and seminars all over India so as to spread awareness regarding realities of HIV/AIDS in India.…”
Section: Awarenessmentioning
confidence: 99%
“…They face various stressors related to their infection, including worries about side effects of medications, stigma and discrimination, about their future and about their general health, among others (Gupta, 2018; Orban et al, 2010; Worthington & Myers, 2003). Prolonged presence of such problems often leads to emotional dysregulation in these adolescents (Brandt et al, 2013; Tiwari, 2015; Qiu et al, 2014; Wei et al, 2016), leading to self-perception issues (Gupta & Sudhesh, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Often called "emotional animals" (Turner, 2007, p.1) [87] , human emotion forms an evaluative basis for future judgments and connections with others (Stephan, 2009). In the emotionally charged, highly evaluative environments of competitive sport (Galli & Gonzalez, 2015) [18] emotional self-regulation impacts on resilience and grit (Gupta & Sudhesh, 2019) [20] . In such sport environments, emotions in sport and from 'non-sport' areas impacts functioning and performance (Friesen et al, 2013) [17] .…”
mentioning
confidence: 99%